Structural, Syntactical and Semantic Data Validation in the Computer Processing of a Medical File - Martin, J. M.; Pointel, J. P.; Martin, J.; Debry, G. (Methods of Information in Medicine, 1976)
Validation of all data in the medical file is indispensable before storage in the computer in order to eliminate errors which may have occurred during data collection and transmission. Formal internal validation checks the observance of spelling and syntax rules governing conversion of medical observations into a form usable by the computer. Internal semantic validation checks the credibility of data by reference to standards. External validation cheeks conformity of the file, printed in clear language, with medical reality.
Keywords: Data Validation; Medical Record; Computer Processing